Performance Measurement Practices in Nepalese Telecommunication Industries - Adhikari, Naba Raj; Chalise, Dhan Raj (Management Dynamics, 2021)
The main aim of this study was to examine the existing performance measurement (PM) practices in the Nepalese telecommunication industries. Nepal Telecom and Ncell have been selected as a sample of the study. Primary data have been collected through structured questionnaires and telephonic interviews using a five-point Likert scale. The study revealed that Nepalese telecommunication industries had used financial and non-financial measures for performance measurement. The financial measure has got significant use and importance than the non-financial measures. Performance measures have been considered a key managerial tool for evaluating performance. The study revealed that performance measures in Nepalese telecommunication industries had been modified when there were changes in the organization's strategies.